Perioperative nursing of a child undergoing islet transplantation followed by kidney transplantation (儿童肾移植后胰岛移植1例的围手术期护理) - LUO Xinchun (罗新春); YE Haidan (叶海丹); CHEN Huilin (陈慧琳) (中西医结合护理)
To review the clinical data and perioperative nursing of a child undergoing islet transplantation followed by kidney transplantation for diabetic mellitus complicated with renal failure. Based on the comprehensive analysis of psychological characteristics and disease condition of the child, preoperative preparation and medication care were carried out. Key issues of postoperative nursing were prevention of portal thrombosis, blood glucose monitoring, prevention of transplant rejection and infection. (本文回顾1例儿童糖尿病合并肾功能衰竭肾移植术后行胰岛移植的临床资料, 总结围手术期护理措施。针对儿童心理特点和病情特点, 术前做好相关准备、用药的护理, 术后做好预防门静脉血栓形成的护理、严密的血糖监测、预防术后排斥反应、感染的护理, 保证患儿术后早期康复。)